Transcriptomics reveal new insights into molecular regulation of nitrogen use efficiency in Solanum melongena. (12th March 2021) - Mauceri, Antonio; Abenavoli, Maria Rosa; Toppino, Laura; Panda, Sayantan; Mercati, Francesco; Aci, Meriem Miyassa; Aharoni, Asaph; Sunseri, Francesco; Rotino, Giuseppe Leonardo; Lupini, Antonio
Abstract : Up-regulation of WRKY33 plays a key role in determining nitrogen-use efficiency in eggplants subjected to low-N stress via an associated gene co-expression network.  Abstract: Nitrogen-use efficiency (NUE) is a complex trait of great interest in breeding programs because through its improvement, high crop yields can be maintained whilst N supply is reduced. In this study, we report a transcriptomic analysis of four NUE-contrasting eggplant ( Solanum melongena ) genotypes following short- and long-term exposure to low N, to identify key genes related to NUE in the roots and shoots. The differentially expressed genes in the high-NUE genotypes are involved in the light-harvesting complex and receptor, a ferredoxin–NADP reductase, a catalase and WRKY33 . These genes were then used as bait for a co-expression gene network analysis in order to identify genes with the same trends in expression. This showed that up-regulation of WRKY33 triggered higher expression of a cluster of 21 genes and also of other genes, many of which were related to N-metabolism, that were able to improve both nitrogen uptake efficiency and nitrogen utilization efficiency, the two components of NUE. We also conducted an independent de novo experiment to validate the significantly higher expression of WRKY33 and its gene cluster in the high-NUE genotypes. Finally, examination of an Arabidopsis transgenic 35S::AtWRKY33 overexpression line showed that it had a bigger root system and was more efficient at taking up N from the soil, confirming the pivotal role of WRKY33 for NUE improvement.